Increases in sensory noise predict attentional disruptions to audiovisual speech perception - Fisher, Victoria L.; Dean, Cassandra L.; Nave, Claire S.; Parkins, Emma V.; Kerkhoff, Willa G.; Kwakye, Leslie D. (Frontiers in Human Neuroscience, 2023)
We receive information about the world around us from multiple senses which combine in a process known as multisensory integration. Multisensory integration has been shown to be dependent on attention; however, the neural mechanisms underlying this effect are poorly understood. The current study investigates whether changes in sensory noise explain the effect of attention on multisensory integration and whether attentional modulations to multisensory integration occur via modality-specific mechanisms. A task based on the McGurk Illusion was used to measure multisensory integration while attention was manipulated via a concurrent auditory or visual task. Sensory noise was measured within modality based on variability in unisensory performance and was used to predict attentional changes to McGurk perception. Consistent with previous studies, reports of the McGurk illusion decreased when accompanied with a secondary task; however, this effect was stronger for the secondary visual (as opposed to auditory) task. While auditory noise was not influenced by either secondary task, visual noise increased with the addition of the secondary visual task specifically. Interestingly, visual noise accounted for significant variability in attentional disruptions to the McGurk illusion. Overall, these results strongly suggest that sensory noise may underlie attentional alterations to multisensory integration in a modality-specific manner. Future studies are needed to determine whether this finding generalizes to other types of multisensory integration and attentional manipulations. This line of research may inform future studies of attentional alterations to sensory processing in neurological disorders, such as Schizophrenia, Autism, and ADHD.